Karakteristik koefisien gesek bantalan rem organik kayu Albizia Chinensis, tingkat keausan dan suhu kerja dengan variasi komposisi - Azamataufiq Budiprasojo; Bayu Rudiyanto (Jurnal Ilmiah Rekayasa Pertanian dan Biosistem, 2023)
The use of organic materials as materials in the automotive industry is increasingly common. For example, the brake pads currently use organic materials. Organic brake pads have the advantage of being quiet, because they contain less metal which will rub against the brake rotor and provide a smoother braking experience because of its resin composition that makes their operation smoother. Although it has many advantages, this pad also has a disadvantage like its low hardness and less temperature resistances that make it is common to replace sooner than expected. This research investigates the wear and temperature of organic brake pads majority made from Albizia chinensis or in bahasa well known as kayu sengon, when used and these compositions are mixed with resin and aluminum and pressure to produce a long use of modern organic brake pads. 1st composition is Polyurethane 40 g, Wood 10 g, Aluminium 40 g, Carbon 10 g; 2nd composition is Polyurethane 40 g, Wood 15 g, Aluminium 30 g, Carbon 15 g; 3rd composition are Polyurethane 40 g, Wood 20 g, Aluminium 20 g, Carbon 20g. The minimum wear is 1.1.10-8 g/sec.mm2 and the maksimum wear is 2.3.10-8 g/sec.mm2 which is still 40% higher than the OEM standard brake pad. The minimum temperature of all organic brake is 129oC and the maksimum temperature is 170oC which is still reach 6% higher than the standard brake pad comparison. The minimum friction coefficient is 0.5 and the maksimum is 0.7 compared to its OEM standard 0.5. References to SNI, this value is in standard range, except the 1st composition.